Intersections between Young Women’s Racial/Ethnic Identities and Sexual Orientation on Rates of Sexual Violence and Substance Use - Norris, Alyssa (Psychol Sex, 2020)
BACKGROUND: Little is known about whether there are differences in rates of sexual violence and its association with substance use based on women’s identities, specifically the intersection of their race/ethnicity and sexual orientation. METHOD: Women (N = 546; 18 to 29 years of age) recruited from a reproductive healthcare clinic reported their race, ethnicity, sexual orientation, sexual violence history and substance use. Five logistic regressions examined (a) rates of sexual violence, and (b) the strength of the associations between sexual violence and four substance use outcomes (heavy alcohol use, marijuana use, cigarette use, number of cigarettes used) based on sexual orientation. Subsequent logistic regressions examined race/ethnicity as a moderator of the associations between sexual orientation and (a) rates of sexual violence and (b) substance use. RESULTS: Most women surveyed were heterosexual (64%), and 35% of all women reported unwanted sex. Sexual minority women (SMW) reported higher rates of sexual violence and substance use than heterosexual women. Sexual violence was more strongly associated with heavy alcohol use, but not with marijuana or cigarette use, for SMW than heterosexual women. Rates of sexual violence varied based on the intersection of sexual orientation and race/ethnicity. Although SMW were more likely to report sexual violence than heterosexual women, this association was weaker for Black/Latinx women than for non-Hispanic White women (aOR = 0.39, 95%CI [0.18, 0.82]). Race/ethnicity did not moderate the strength of associations between sexual violence and substance use. CONCLUSIONS: SMW exhibit increased risk for sexual violence and substance use, and victimization was associated with heavy alcohol use. Few racial/ethnic differences emerged as a function of sexual orientation, so SMW are a group with unique needs around sexual violence experiences and substance use, regardless of race/ethnicity. Healthcare providers should be aware of the link between substance use and prior victimization when treating SMW.